Pengaruh Daya Saing Negara terhadap Keterbukaan Dagang di ASEAN - Raphael Gunawan Hasudungan; Agustina Suparyati (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2020)
This study aims to analyze the relationship between variables determinant of nation’s competitiveness based on the first subclass of the Global Competitiveness Report (GCR) produced by World Economic Forum (WEF) which discusses relations between infrastructure, economics and education, and health with trade openness. The study uses secondary data that is processed and generated by WEF of each nation competitiveness variables of the GCR. The analytical method used is panel data regression with 6 countries in Southeast Asian (ASEAN) region as the object in the period of 2008 to 2016. The limitations of this study are the limited data and objects used. The results from this research showed the only variable which significantly affects trade openness that also has a positive impact on it is institution.